Inovasi Pemberian Makanan Tambahan Nugget Patin Daun Kelor sebagai Upaya Pencegahan Stunting - Erianti, Anggie; Cholifah, Siti (Universitas Baiturrahim, 2025)
Stunting is a serious health issue caused by chronic malnutrition during the first 1,000 days of life. In Tambak Kalisogo village, 8% of 150 toddlers are identified as stunted. The impacts of stunting include reduced cognitive and intellectual abilities in children and an increased risk of diseases in adulthood. One way to address stunting is by providing supplementary food high in protein and containing zinc. Tambak Kalisogo village is a major fish farming area in the Sidoarjo region. Considering the human resources in Tambak Kalisogo village, which are rich in the fisheries sector, the aim of this community service initiative is to innovate by providing supplementary food in the form of patin fish and moringa leaf nuggets for children identified as stunted. The methods used include conducting surveys, planning activities, anthropometric measurements (height, weight, and body mass index), and providing supplementary food. The results of the initiative showed that patin fish and moringa leaf nuggets were highly favored by children due to their texture and delicious taste. These nuggets are rich in essential nutrients such as protein and fiber, making them effective in preventing stunting. The community responded positively to this program and expressed an initiative to replicate the innovation of providing supplementary food.